Assessment of radiation forcing data sets for large-scale sea ice models in the Southern Ocean - Vancoppenolle, M.; Timmermann, R.; Ackley, S.F.; Fichefet, T.; Goosse, H.; Heil, P.; Lieser, J.; Leonard, K. C.; Nicolaus, M.; Papakyriakou, T.; Tison, J.-L. (Deep Sea Research Part II: Topical Studies in Oceanography, 2011)
International audience no abstract